PENERAPAN SANKSI PIDANA DENDA TERHADAP PELAKU KEJAHATAN NARKOTIKA (Studi Kasus Pendapat Hakim Di Pengadilan Negeri Kendari) - Muhammad Asrianto Zainal (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2017)
The study aims to analyse the opinion of a judge about fine penalty in narcotics’s case at Kendari’s court, how to determine the application of fine penalty in narcotics’s case, and the prospects of criminal penalties in the future. In this study, the authors employed a descriptive qualitative design by conducting interviews to collect the primary data and a library research to obtain secondary data and the documentation. Research findings showed that there are some major perceptions of judge in considering fine penalty. One of them is to aggravate the sanctions against offenders. Meanwhile, based on the government point of view, the majority of judges found that the fine penalty becomes the income for the government, and others argue that it helps to reduce the excess capacity of prison which indeed decreases the government burdens in this aspect. However, infact, when the judges decide the penalty, they often do not follow the regulation and even give lighter punishment for narcotics criminal than which is stated on the law. In addition, the fine payment in the future will be more established because of  the payment of criminal fines in the future can be paid through installments.